The drivers of diaspora donations for development: Evidence from the Philippines - Victoria Licuanan; Toman Omar Mahmoud; Andreas Steinmayr (Kiel Institute for the World Economy (IfW), 2012)
Little is known about the drivers of migrant donations to their home countries. Using data on all donations from Filipino migrants administered by the Philippine Commission on Filipinos Overseas between 1990 and 2010, this paper explores which host and home country factors are associated with migrant donations. On the host country side, we find that donations increase with the level of income earned by the Filipino diaspora and with the number of hate crimes against minorities. On the home country side, we find that donations are not well-targeted. As donations mainly flow to provinces with high rates of emigration, they do not reach the least developed Philippine provinces. However, the diaspora is responsive to natural disasters and channels donations to provinces when they are hit by a typhoon.
Keywords: F22; F24; 330; international migration; philanthropy; collective remittances